Dignidade na ordem econômica: o capitalismo humanista como dimensão econômica dos direitos humanos - Rabelo, Carolina Gladyer (2018)
This thesis aims to study the human dignity within the framework of the Brazilian constitutional economic order, which affirmed it as its purpose. Our proposal, based on a fraternal view, consists the search for the effectiveness of this principle in the context of the current capitalist system. The analysis is based on the multidimensionality of human rights, which according to the Theory of Humanist Capitalism – used as a methodological postulate of this work, comprises an indissoluble consolidation of the three dimensions of human rights, linked to: freedom, equality and fraternity. In today's world, where changes occur at the speed of light, there is no more space for a Cartesian thinking, where each discipline remains restricted to its field of activity. Law, a conjectural science par excellence, is not oblivious to such a finding. Therefore, we understand that the problem brought must be a subject of study through other optics, such as Quantum Physics, which understands the interconnection of factors and the awareness of coexistence. Thus, firstly, we will treat the methodological bases used, which contemplate Normative Jus-humanism and Humanist Capitalism, as well as the reinforcements inherent in the Theory of Morphic Fields, Quantum Mechanics and the Theory of Quantum Law. In the next section, we propose an analysis focused on the concept of human dignity and its relation with human rights. Following, using the assumptions presented, we defend the satisfaction of human dignity as a tangible objective, through the recognition of humanist capitalism as the economic dimension of human rights, by its philosophical bases and its legal-economic systematic